Life Cycle Cost Analysis (LCCA) on Excavators for Earthwork (Excavation and Earthmoving) in a Highway Project. - Zulkiflee, Muhammad Hilman (Universiti Teknologi PETRONAS, 2020)
Earthwork activities such as excavation and earthmoving represent a huge portion of the process for road and ground highway construction. Furthermore, highway construction is a very expensive project with minimal returns with the main purpose of providing quality traveling experience to its users. Fortunately, many studies have proven various methods can be used to analyze and minimize the overall cost of earthwork in highway construction through plan optimization followed by a life cycle cost analysis (LCCA). This study aims to provide a detailed life cycle cost analysis on earthwork activities for highway construction in order to find out the most economical choice from different alternative excavator models to minimize cost and other decision-making processes. Based on literature reviews done on other LCCA papers, it is completely possible to analyze the life cycle cost of these excavators from a superficial case study on a proposed earthmoving work.